2021
DOI: 10.1093/ee/nvab116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet and Temperature on the Life History of the Redlegged Ham Beetle (Coleoptera: Cleridae)

Abstract: We investigated the effects of various foods and different rearing temperatures on the survival and development of the redlegged ham beetle Necrobia rufipes (De Geer) (Coleoptera: Cleridae), a serious pest of dry-cured hams. The diets tested were dried pet food, finely shredded copra, shredded cheese, dry-cured ham, ground fish meal, and mature larvae of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae). As indicated by the growth index and k-values, N. rufipes populations grew fastest on the pet food a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…According to Simmong and Elington [35] the life cycle of N. ru pes varies in connection with climatic conditions. When we take into account the longevity of N. ru pes on pig substrate, our results are similar to those of Hasan et al 2022 [42] at 27°C who used eight kind of substrate and combination to fed N. ru pes to access the longevity. They showed that the longevity of N. ru pes is in uenced by temperature.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…According to Simmong and Elington [35] the life cycle of N. ru pes varies in connection with climatic conditions. When we take into account the longevity of N. ru pes on pig substrate, our results are similar to those of Hasan et al 2022 [42] at 27°C who used eight kind of substrate and combination to fed N. ru pes to access the longevity. They showed that the longevity of N. ru pes is in uenced by temperature.…”
Section: Discussionsupporting
confidence: 87%
“…Food availability and photoperiod also affect incubation time. Hasan M. et al [42] investigated effects of various foods and different rearing temperatures on the survival and development of N. ru pes. This beetle populations grew fastest on the pet food and slowest on the copra.…”
Section: Discussionmentioning
confidence: 99%